A chemo-mechanical coupling model of oxidation and interlayer cracking of copper nanowires. (May 2023) - Gong, Yulong; Yan, Xin; Wen, Jici; Meng, Qinghua; Li, Ang; Shi, Xinghua
Abstract: Copper nanowires have received extensive attention for their potential applications in optics, electricity and catalysis, while oxidation erosion has become the biggest obstacle to their widespread application. Here, we present a chemo-mechanical coupling model to investigate the interlayer cracking behaviors of nanowires during oxidation. In contrast to existing chemo-mechanical models, the present model emphasizes that the process of oxygen entry into copper nanowires is chemical reaction-mediated layer-by-layer replacement rather than vacancy-mediated diffusion, which means the oxygen ions in the outer layer would not cross over the oxygen atoms in the inner layer during their entry. These conclusions are validated by molecular dynamics simulations. We then discuss the effect of the chemical reaction-induced free energy on the stress state of the nanowire during the reaction. Finally, a self-developed finite difference procedure is used to solve the control equations and the fracture location is determined according to the energy release rate analysis. We find the fracture of nanowires is closely dependent on the size of nanowire, the reaction rate and the oxygen concentration. This work deepens our understanding of the mechanism of chemo-mechanical coupling and fracture behavior of metals due to oxidation, thus has implications in other areas involving chemo-mechanical coupling.